Case report: Successful use of mepolizumab for immune checkpoint inhibitors–induced hypereosinophilic syndrome in two patients with solid malignancies - Lazzari, Chiara; Yacoub, Mona Rita; Campochiaro, Corrado; Bulotta, Alessandra; Palumbo, Diego; Ogliari, Francesca Rita; Dagna, Lorenzo; Marchesi, Silvia; Ponzoni, Maurilio; Gregorc, Vanesa (Frontiers in Oncology, 2023)
Hypereosinophilic syndrome (HES) represents a group of blood disorders characterized by an absolute eosinophil count (AEC) >1.5 × 103/μL in the peripheral blood, which eventually extravasate and cause organ damage. It can be primary or secondary to infections or tumors. The infiltration of eosinophils in tissue and organs is associated with different disorders, and in some cases with life-threatening manifestations. Albeit the pathogenesis of HES in patients with solid tumors is not yet clarified, recently HES has also been described as an immune-related adverse event in patients with solid tumors receiving immune checkpoint inhibitors. Treatment of HES is still debated, especially in patients with concomitant solid tumors, and different drugs including imatinib, hydroxyurea, interferon-ɑ, glucocorticoids, the monoclonal antibody targeting circulating IL-5 mepolizumab have been proposed according to the underlying cause and the severity of HES. Herein we describe, for the first time, the successful use of mepolizumab for the treatment of immunecheckpoint-induced HES in two patients with metastatic solid tumor.